André Naud: From Vatican II to Simone Weil. (10th December 2019) - Schmidt, Lawrence
Abstract: André Naud was a French‐Canadian Catholic theologian who served as a peritus or advisor to Cardinal Leger, the Archbishop of Montreal at the Second Vatican Council between 1962 and 1965. Naud's entire theological career was informed by the teachings of the Council. This was the reason why during the Papacy of John Paul II after 1978 he became alarmed at the expansion and the distortion of the authority of the magisterium. Over the last fifteen years of his life, he wrote three remarkable books on this theme. In the last book (2002) entitled Les Dogmes et le Respect de l'Intelligence: Plaidoyer Inspiré par Simone Weil (The Dogmas and the Respect for Intelligence: An Argument Inspired by Simone Weil), he undertook an in‐depth analysis of Simone Weil, who had argued in the 1940s that Catholicism was in need of a philosophical cleaning up. This paper elaborates and explains the particular ways that Weil's writings helped Naud to reformulate in the spirit of the Second Vatican Council the role of the magisterium with regard to dogmatic formulations, the manner of the reception of that teaching, the inspiration of scripture, the interpretation of miracles and the understanding of the Church itself.